Odpowiedź :
) a⁶×(a³÷a²) = a⁶×a=a⁷
założenie a ≠ 0
b) (b⁷÷b⁴)²×b= b³×b=b⁴
założenie b ≠ 0
c) (x¹²):(x²×x)= x¹²:x³=x⁹
założeniex różne od 0
d. (y¹⁰:y²)²÷(y³×y²)= y⁸:y⁵=y³
założenie y różne od 0
założenie a ≠ 0
b) (b⁷÷b⁴)²×b= b³×b=b⁴
założenie b ≠ 0
c) (x¹²):(x²×x)= x¹²:x³=x⁹
założeniex różne od 0
d. (y¹⁰:y²)²÷(y³×y²)= y⁸:y⁵=y³
założenie y różne od 0
) a⁶*(a³/a²) = a⁶*a=a⁷
założenie a ≠ 0
b) (b⁷/b⁴)²*b= b³*b=b⁴
założenie b ≠ 0
c) (x¹²)/(x²*x)= x¹²/x³=x⁹
założenie x ≠ 0
d. (y¹⁰/y²)²/(y³*y²)= y⁸/y⁵=y³
założenie y ≠ 0
założenie a ≠ 0
b) (b⁷/b⁴)²*b= b³*b=b⁴
założenie b ≠ 0
c) (x¹²)/(x²*x)= x¹²/x³=x⁹
założenie x ≠ 0
d. (y¹⁰/y²)²/(y³*y²)= y⁸/y⁵=y³
założenie y ≠ 0
) a⁶*(a³/a²) = a⁶*a=a⁷
założenie a ≠ 0
b (b⁷/b⁴)²*b= b³*b=b⁴
założenie b ≠ 0
c (x¹²)/(x²*x)= x¹²/x³=x⁹
założenie x ≠ 0
d (y¹⁰/y²)²/(y³*y²)= y⁸/y⁵=y³
założenie y ≠ 0
założenie a ≠ 0
b (b⁷/b⁴)²*b= b³*b=b⁴
założenie b ≠ 0
c (x¹²)/(x²*x)= x¹²/x³=x⁹
założenie x ≠ 0
d (y¹⁰/y²)²/(y³*y²)= y⁸/y⁵=y³
założenie y ≠ 0